Effect of Fe3+ on the nutrient removal performance and microbial community in a biofilm system - Wu, Tong; Zhong, Le; Pang, Ji-Wei; Ren, Nan-Qi; Ding, Jie; Yang, Shan-Shan (Frontiers in Microbiology, 2023)
In this study, the influence of Fe3+ on N removal, microbial assembly, and species interactions in a biofilm system was determined. The results showed that maximum efficiencies of ammonia nitrogen (NH4+-N), total nitrogen (TN), phosphorus (P), and chemical oxygen demand (COD) removal were achieved using 10 mg/L Fe3+, reaching values of 100, 78.85, 100, and 95.8%, respectively, whereas at concentrations of 15 and 30 mg/L Fe3+ suppressed the removal of NH4+-N, TN, and COD. In terms of absolute abundance, the expression of bacterial amoA, narG, nirK, and napA was maximal in the presence of 10 mg/L Fe3+ (9.18 × 105, 8.58 × 108, 1.09 × 108, and 1.07 × 109 copies/g dry weight, respectively). Irrespective of Fe3+ concentrations, the P removal efficiency remained at almost 100%. Candidatus_Competibacter (10.26–23.32%) was identified as the most abundant bacterial genus within the system. Determinism (50%) and stochasticity (50%) contributed equally to microbial community assembly. Co-occurrence network analysis revealed that in the presence of Fe3+, 60.94% of OTUs in the biofilm system exhibited positive interactions, whereas 39.06% exhibited negative interactions. Within the OTU-based co-occurrence network, fourteen species were identified as key microbes. The stability of the system was found to be predominantly shaped by microbial cooperation, complemented by competition for resources or niche incompatibility. The results of this study suggested that during chemical P removal in wastewater treatment plants using biofilm methods, the concentration of supplemental Fe3+ should be maintained at 10 mg/L, which would not only contribute to P elimination, but also enhance N and COD removal.